Progressivism Beliefs and Goals in English Learning and Teaching Related Merdeka Curriculum: A PRISMA-Guided Systematic Literature Review - Abraham Adiel Yudhawastu Pramuyda; Ilza Mayuni; Bambang Nur Alamsyah Lubis; Martjin Van Driel (Attractive : Innovative Education Journal, 2026)
Progressivism, often associated with Deweyan “learning by doing”, democratic classrooms, and the primacy of learners’ interests, has re-emerged as an implicit philosophical foundation of Indonesia’s recent curriculum reform, particularly the Merdeka Curriculum and the Merdeka Belajar–Kampus Merdeka (MBKM) policy. Yet empirical and conceptual evidence about how progressivism beliefs and goals are translated into English language teaching (ELT) across Indonesian schooling and higher education remains fragmented. This study, therefore conducts a PRISMA-guided systematic literature review (SLR) to synthesise progressivism beliefs (what teachers, curricula, and institutions assume about learning and learners) and progressivism goals (what outcomes are prioritised) in ELT related to the Merdeka Curriculum. Following a PRISMA-P-informed protocol, we applied a PICOC framework to develop search strings and eligibility criteria, and screened publications (2017–2025) from ScienceDirect, DOAJ, ERIC, Google Scholar, and Indonesian peer-reviewed journal portals. After de-duplication, title abstract screening, full text assessment, and quality appraisal using the Mixed Methods Appraisal Tool (MMAT), 27 studies were included for thematic synthesis. The review identifies five convergent themes: (1) learner agency and autonomy as a core belief and goal; (2) experiential and inquiry driven ELT through project/problem/task based learning; (3) authentic, formative, and performance based assessment practices; (4) character, civic, and intercultural formation aligned with the Pancasila Student Profile; and (5) teacher role transformation from knowledge transmitter to designer, facilitator, and reflective practitioner. However, the evidence also highlights persistent constraints teacher readiness, assessment literacy, resource inequity, and policy practice misalignment that weaken progressivist enactment. The novelty of this SLR lies in its explicit mapping of progressivism constructs to Merdeka Curriculum ELT practices, producing a practical framework for curriculum implementation, teacher education, and research.